Comparative toxicity of endosulfan and diazinon on the embryo-larval development of the South American toad, Rhinella arenarum - Aronzon, Carolina Mariel (2017)
The toxicity of endosulfan and diazinon were comparatively analyzed on the early development of the South American toad, Rhinella arenarum. Pesticides varied greatly in their effects on survival, with concentration-, time- and stage-dependent sensitivity. Endosulfan was 227 times more toxic than diazinon. The larval period was the most sensitive for both pesticides (LC-504h: 0.01mgL-1 and 1.92mgL-1 for endosulfan and diazinon, respectively). Endosulfan toxicity increased 587 and 60 times from acute to chronic exposure in treatments with embryos and larvae, respectively while diazinon toxicity increased about 4 and 5 times, respectively. Both pesticides caused important neurotoxic effects expressed as behavioral disturbances. Risk evaluation assessed by Hazard Quotient (HQ) was over 1, the level of concern, for both pesticides at chronic exposure periods and even at acute endosulfan exposure. Results obtained in the present study, highlight that these pesticides should be considered potential threats for this species.